1999
DOI: 10.1111/j.1600-065x.1999.tb01348.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines and passive immunological approaches for the control of fertility and hormone‐dependent cancers

Abstract: Reviewed here is the development of a vaccine against the human chorionic gonadotropin that prevents pregnancy in sexually active women without impairment of ovulation or derangement of menstrual regularity. Also reviewed are the vaccines inducing antibodies against the luteinizing hormone-releasing hormone, which have immunotherapeutic potential in prostatic hypertrophy and other sex hormone-dependent male and female cancers. The adoption of passive immunization using humanized recombinant antihormone antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…The other members of the family are luteinising hormone (LH), follicle-stimulating hormone (FSH) and thyroid-stimulating hormone (TSH). Even though each carries a hormone-unique β-chain, there is extensive sequence homology between the β-chains of hCG and LH leading to the production of LH-cross-reactive antibodies following vaccination with the intact hCG β-chain [24]. However, the carboxy-terminal region of the hCG β-chain, referred to as the Cterminal peptide (CTP), is a unique feature of hCG.…”
Section: Human Chorionic Gonadotropin (Hcg)mentioning
confidence: 99%
See 3 more Smart Citations
“…The other members of the family are luteinising hormone (LH), follicle-stimulating hormone (FSH) and thyroid-stimulating hormone (TSH). Even though each carries a hormone-unique β-chain, there is extensive sequence homology between the β-chains of hCG and LH leading to the production of LH-cross-reactive antibodies following vaccination with the intact hCG β-chain [24]. However, the carboxy-terminal region of the hCG β-chain, referred to as the Cterminal peptide (CTP), is a unique feature of hCG.…”
Section: Human Chorionic Gonadotropin (Hcg)mentioning
confidence: 99%
“…The HSD vaccine was therefore extremely successful in preventing pregnancy, but only in the moderate to high antibody responders. Although this has been the only phase II clinical trial of a contraceptive vaccine so far, the HSD trial was of extreme importance because it established the efficacy of a vaccine approach for protecting against undesired pregnancy [24].…”
Section: Human Chorionic Gonadotropin (Hcg)mentioning
confidence: 99%
See 2 more Smart Citations
“…An active area of research is the development of synthetic GnRH-based vaccines against reproductive hormone-dependent male and female cancers. 1 Studies have shown that immunisation against GnRH can reduce prostate levels of testosterone similar to surgical castration in numerous mammalian models, including mice and humans. 2,3 Immunisation of both males and females against GnRH can have a profound effect on fertility through the reduction in sex steroids and cessation of gametogenesis.…”
Section: Introductionmentioning
confidence: 99%